Preferences over Relative Income within the Household - Johannes Hermle; Elena Herold; Nikolaus Hildebrand (Institute of Labor Economics (IZA), 2024)
What preferences do partners hold over their relative income within the household? We provide a flexible framework of preferences over relative income within the household that captures various motives, including inequality aversion and a preference for being the primary earner. We study the role of these preferences for marital selection, separation and household public good provision in a marriage market matching model with search frictions. We test the model predictions using large administrative tax data from Germany. We document the existence of a kink point in the relative income distribution at the point of spousal income equality, consistent with the presence of kinked preferences over relative income. We also find the presence of a convex kink in wives' household public good provision, suggesting that women bear the incidence of spousal relative income preferences. To disentangle the preferences of women and men, we implement a survey experiment. Our results indicate that women exhibit inequality aversion while men exhibit a preference for being the primary earner.
Keywords: D63; D64; D91; J12; J16; 330; relative income concerns; relative income distribution